Pelatihan Literasi Keuangan Dan Literasi Digital Kepada Pelaku Usaha Mikro Dan Kecil Di Kota/Kabupaten Jayapura - Hastutie Noor Andriati; Kurniawan Patma (The Community Engagement Journal, 2020)
Good financial management is still considered as something that is not important because there is no awareness from micro and small businesses. Therefore, the idea arises that financial and digital literacy should be life skills that must be provided to micro and small businesses in Jayapura. Financial literacy education in micro and small business is a concept about the introduction of financial management wisely in order to be able to manage finance well, control financial expenditures by distinguishing which ones are needs and which are just wishes. Financial literacy and digital literacy mentoring activities have been carried out by getting excellent attention from participants by requesting the same activities can be done as follow up. Also, it has delivered several discussions about daily and monthly cash books as well as simple Financial Statement at the end of the year for dormitories.